Pengaruh Model Bleanded Learning Terhadap Hasil Belajar Tematik Terpadu di Tinjau dari Kemandirian Siswa kelas IV - Mulyati, Asrina; Wahyuni, Alfira (LP2M Universitas Adzkia, 2023)
This research is motivated by several problems, namely: Teachers are less creative in conducting the online learning process, student learning outcomes are not optimal, students are less independent in the learning process,Model Blended Learning in integrated thematic learning has not been applied optimally. The purpose of this study was to determine student learning outcomes in terms of student learning independence by using thelearning model Blended Learning in integrated thematic learning subjects. The method used in this research was Quasi Experimental Design, the design of this study is Posttest Only Control Group Design. The results of this study are seen from the results of hypothesis testing with t-test and show tcount= 4,557 and ttable= 2,026 with dk = 37 (n1 + n2 – 2 = 20 + 19 – 2 = 37) and a significant level of 5%. Based on the t-test> t-table (4.557>2.026). So it can be concluded there is a significant effect of using themodel Blended Learning on integrated thematic learning outcomes in terms of student learning independence.